EP503 Real world outcomes of advanced endometrial cancer treated with neoadjuvant chemotherapy. (1st November 2019) - Baillie, K; Cunningham, C; Crearie, C; Laskey, J; Bennie, M; Burton, K; Sadozye, A; Lindsay, R; Harrand, R; Siddiqui, N; Reed, N; Graham, K
Abstract : Introduction/Background: Neoadjuvant chemotherapy (NACT) is increasingly used in locally advanced or selected stage 4B endometrial cancer that is considered unsuitable for primary surgery, despite the lack of randomised evidence. In the West of Scotland Cancer Network (WoSCAN), NACT is offered to women with inoperable locally advanced disease or limited stage 4B disease (omental/peritoneal involvement and/or small volume lung metastases/pleural effusion). This study aimed to identify the proportion of patients proceeding to delayed primary surgery or interval debulking surgery following NACT for endometrial cancer and evaluate survival outcomes. Methodology: Data were collected retrospectively from electronic clinical records of WoSCAN patients who commenced NACT between January 2012 and December 2016. Statistical analysis was performed using R®. OS was estimated using Kaplan-Meier method and Cox's proportional-hazards models used to calculate unadjusted hazard ratios (HR). Results: 54 patients were identified; median age was 67 years (range 36–85). All women had Stage III (57.4%) or IV (42.6%) disease. Pathological subtype consisted of serous (42.6%), endometrioid (31.5%), or other (25.9%). NACT regimen was almost exclusively Carboplatin/ Paclitaxel (92.6%); a median of 4 cycles were administered (range 1-6). 66.7% proceeded to surgery, 7.4% received primary (chemo)radiotherapy, and 25.9% received no definitive therapy. Of the 36 patients who underwent surgery, 83.3% received adjuvant radiotherapy. Data were censored in February 2018 at which time 33.3% were alive. Median OS was 31.12 months (95% CI 24.93–58.49); 40.8 months (95% CI 25.6 - Not reached) in the surgical cohort versus 18.6 months (95% CI 8.1–60.6) in patients who received NACT alone (HR 2.28 (95% CI 1.14–4.56)). Conclusion: 66.7% of women proceeded to surgery following NACT. Median OS is significantly improved with surgery compared to NACT alone. NACT is a valid option in patients with advanced endometrial cancer who are not suitable for primary surgery. Disclosure: Nothing to disclose.